Regulating Australia's 'Gangmasters' through Labour Hire Licensing. (September 2019) - Forsyth, Anthony
This article examines the recent introduction of state-based regulation to address the increasingly prominent problem of exploitation of vulnerable workers by labour hire providers around Australia. Mounting evidence of underpayments and other breaches of workplace laws has emerged from a range of state and federal inquiries into the labour hire sector in recent years. The article draws parallels between these abuses and the exploitative activities of 'gangmasters' in industrial-era Britain. It then closely analyses and compares the labour hire licensing schemes introduced in Victoria, Queensland and South Australia, which aim to combat noncompliance by introducing barriers to entry and eliminate 'rogue' operators from the labour hire market. The article assesses the effectiveness of similar licensing and registration schemes in several overseas jurisdictions, especially the gangmasters licensing scheme operating in the United Kingdom since 2004. The article concludes that the licensing schemes introduced under the three state laws are a timely and, most likely, effective new approach to tackling the problem of noncompliance with workplace and other laws. Alternative responses to exploitation at the federal level are also considered, including the 2017 Vulnerable Workers legislation introduced largely in response to systemic underpayments in the 7-Eleven franchise network. Finally, the article observes that federal reform of the labour hire sector may emerge in the near future, given the Labor Opposition's policy commitment to introduce a national labour hire licensing scheme. In the meantime, the state labour hire licensing schemes examined in this article represent an important step forward in regulation to combat worker exploitation by contemporary Australian 'gangmasters'.